Changing Consumption Patterns of Bamboo shoots: A Case Study of Traditional Food-Related Knowledge Systems - Poonam Singhal; Ranjay Singh; Santosh Satya; S N Naik (International Journal on Food, Agriculture and Natural Resources, 2022)
Bamboo shoots form an integral part of the local diet of the Northeastern states of India. Fermented shoots have been consumed by tribal communities since ancient times. However, with increasing globalization and fast-food consumption, the traditional knowledge and skills of processing bamboo shoots seem to be changing. This paper highlights the changes in processing ways over the years in the younger generation. Data were collected using an unstructured interview schedule and observation through home visits from Adi women of four villages namely Balek, Sibut, Runne, and Mirbuk in Pasighat Block of Arunachal Pradesh. It was observed that some newer practices of processing bamboo shoots had been adopted while ignoring the traditional practices which emphasized eliminating toxicity in bamboo shoots.